2021
DOI: 10.3390/vaccines9121461
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions and Acceptance of COVID-19 Booster Vaccination in China: A Cross-Sectional Study

Abstract: Coronavirus disease 2019 (COVID-19) booster vaccination has been proposed in response to the new challenges of highly contagious variants, yet few studies have examined public acceptance of boosters. This study examined public acceptance of COVID-19 booster vaccination and its influencing factors by using the data from a self-administered online cross-sectional survey conducted in June 2021 in China. Multiple logistic analysis was used to examine the influencing factors of booster acceptance based on the healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
112
3
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(131 citation statements)
references
References 45 publications
13
112
3
3
Order By: Relevance
“…This construct can be influenced by both policies and the availability of boosters. This finding mirrors the results from the plethora of studies on vaccine hesitancy conducted before the rollout of COVID-19 vaccines and during the rollout of the primary series of vaccines [ 22 , 25 , 26 , 39 , 40 , 41 ]. This indicates a need for sustained and ongoing culturally relevant communication regarding the benefits of these vaccines and their usefulness along with efforts to reduce barriers and perceived disadvantages of these vaccines and their booster doses.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This construct can be influenced by both policies and the availability of boosters. This finding mirrors the results from the plethora of studies on vaccine hesitancy conducted before the rollout of COVID-19 vaccines and during the rollout of the primary series of vaccines [ 22 , 25 , 26 , 39 , 40 , 41 ]. This indicates a need for sustained and ongoing culturally relevant communication regarding the benefits of these vaccines and their usefulness along with efforts to reduce barriers and perceived disadvantages of these vaccines and their booster doses.…”
Section: Discussionsupporting
confidence: 78%
“…This indicates a need for sustained and ongoing culturally relevant communication regarding the benefits of these vaccines and their usefulness along with efforts to reduce barriers and perceived disadvantages of these vaccines and their booster doses. Regarding booster doses, vaccine and pandemic fatigue, side effects from prior doses, breakthrough infections, and lower perceived risk of the disease with declining cases of infections could lead to questioning by the public about the utility and need of the boosters, their effectiveness, and whether boosters are a viable solution for pandemic control [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yadete et al ( 35 ) found that about 62% of a representative sample of the American adult population accepted COVID-19 VB in July 2021 ( 35 ). On the other hand, 84.8% of the Chinese adults were willing to receive COVID-19 VB in June 2021, and 88.9% of the American medical students were in favor of receiving COVID-19 VB in Spring 2021 ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…This review included studies measuring either general COVID-19 vaccination intention or behaviour or behaviour relating to receiving the first dose but was conducted before the subsequent booster vaccination roll out. While there is no a priori reason to expect that interventions reported herein would be widely ineffective if applied to the context of booster vaccination (indeed, some of the interventions identified above echo barriers and facilitators identified in the pre-COVID-19 vaccination literature [ 71 , 72 ] and the preliminary global insights on booster vaccinations [ 73 , 74 ]), further review work is recommended to bolster the evidence base for effective vaccination interventions. This is particularly pertinent given the novelty of COVID-19 booster vaccinations.…”
Section: Limitationsmentioning
confidence: 99%